Pemberian Informasi tentang Manajemen Waktu pada Mahasiswa Organisasi BEM Fakultas Psikologi UNM - Novita Maulidya Jalal; Syamsul Bakhri Gaffar; Ismalandari Ismail; Muhrajan Piara; St. Hadjar Nurul Istiqamah (Literasi Nusantara Publisher, 2022)
Organizational students as students who play an active role and have a role or responsibility within the organization are faced with the choice of lectures and the implementation of organizational programs that require student skills in managing their time. optimal role in the organization and in lectures. The method used in carrying out this program is psychoeducation by providing information related to time management. time management, time management techniques, and strategies for using time management in lectures and organizations. Based on the results of the service, it is recommended that the provision of information about time management be carried out in a longer duration to obtain a conducive time so that it can provide opportunities for organizational students to carry out simulations in making their respective time management before practicing it in their daily life while studying in college and in organizations. So, it can be concluded that time management for organizational activist students is very important so that students can manage their time well with the strategies applied by each individual.